Describing the spine surgery learning curve during the first two years of independent practice. Issue 41 (15th October 2021) - Ferguson, Devin P.; Stevens, Madison T.; Stewart, Samuel A.; Oxner, William M.; Dunning, Cynthia E.; Glennie, R. Andrew
Abstract : Abstract: Retrospective cohort study To characterize the learning curve of a spine surgeon during the first 2 years of independent practice by comparing to an experienced colleague. To stratify learning curves based on procedure to evaluate the effect of experience on surgical complexity. The learning curve for spine surgery is difficult to quantify, but is useful information for hospital administrators/surgical programs/new graduates, so appropriate expectations and accommodations are considered. Data from a retrospective cohort (2014–2016) were analyzed at a quaternary academic institution servicing a geographically-isolated, mostly rural area. Procedures included anterior cervical discectomy and fusion, posterior cervical decompression and stabilization, single and 2-level posterior lumbar interbody fusion, lumbar discectomy, and laminectomy. Data related to patient demographics, after-hours surgery, and revision surgery were collected. Operative time was the primary outcome measure, with secondary measures including cerebrospinal fluid leak and early re-operation. Time periods were stratified into 6 month quarters (quarter [Q] 1–Q4), with STATA software used for statistical analysis. There were 626 patients meeting inclusion criteria. The senior surgeon had similar operative times throughout the study. The new surgeon demonstrated a decrease in operative time from Q1 to Q4 (158 minutes–119 minutes, P  < .05); however, the mean operative time was shorter for the senior surgeon at 2 years (91 minutes, P  < .05). The senior surgeon performed more revision surgeries (odds ratio [OR] 2.5 [95% confidence interval [CI] 1.7–3.6]; P  < .001). Posterior interbody fusion times remained longer for the new surgeon, while laminectomy surgery was similar to the senior surgeon by 2 years. There were no differences in rates of cerebrospinal fluid leak (OR 1.2 [95% CI 0.6–2.5]; P  > .05), nor reoperation (OR 1.16 [95% CI 0.7–1.9]; P  > .05) between surgeons. A significant learning curve exists starting spine practice and likely extends beyond the first 2 years for elective operations.